Treasury Single Account : An Essential Tool for Government Cash Management - Fainboim Yaker, Israel (Technical Notes and Manuals; Technical Notes and Manuals, 2011)
This technical note and manual addresses the following main issues: 1. Discusses the problems of fragmented government banking arrangements and how a treasury single account (TSA) could address them. 2. Explains the concept of a TSA and describes its features. 3. Discusses the design issues that need to be considered in setting up a TSA system. 4. Discusses the preconditions and key sequencing and implementation issues that need to be addressed in establishing a TSA.